A Borane-Catalyzed Metal-Free Hydrosilylation of Chromones and Flavones - Ren, Xiaoyu; Han, Caifang; Feng, Xiangqing; Du, Haifeng (Synlett, 2017)
A Piers-type hydrosilylation of chromones and flavones has been successfully realized for the first time using 0.1 mol % of borane catalyst generated in situ by hydroboration of pentafluorostyrene with HB(C6F5)2 to afford a variety of chromanones and flavanones in 60–99% yields. An attempt for the asymmetric transformation with chiral diyne and HB(C6F5)2 gave chromanones and flavanones in high yields with up to 32% ee.
Keywords: hydrosilylation; chromones; flavones; chromanones; flavanones; borane catalyst; alkene; chiral diyne